The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/jbm.a.34838
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid scaffolds of gelatin–siloxane releasing stromal derived factor‐1 effective for cell recruitment

Abstract: Scaffolds with the capacity to deliver signaling molecules are attractive for bone regeneration. Here, we developed bioactive siloxane-gelatin hybrid scaffolds via a sol gel process containing stromal derived factor-1 (SDF-1) to recruit osteoprogenitor/stem cells. The process was undertaken under room temperature aqueous conditions, which enabled therapeutic molecules to be effectively incorporated. After the sol-gel reaction and lyophilization process, well-crosslinked hybrid scaffolds were obtained with poro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…As aforementioned, SDF-1 is a powerful chemokine, which directly induces cell migration in various cell types including NSC, MSC and so on. In our previous study, SDF-1 loaded scaffolds significantly enhanced cell migration (17). Similarly, SDF-1 significantly enhanced the migration of PC-12 cells in the present study.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…As aforementioned, SDF-1 is a powerful chemokine, which directly induces cell migration in various cell types including NSC, MSC and so on. In our previous study, SDF-1 loaded scaffolds significantly enhanced cell migration (17). Similarly, SDF-1 significantly enhanced the migration of PC-12 cells in the present study.…”
Section: Discussionsupporting
confidence: 84%
“…Construction of expression plasmids. Recombinant SDF-1 protein was constructed as described previously (17). Briefly, the human SDF-1 sequence was amplified by PCR (Perkin Elmer, Inc.) using primers flanked with restriction sites for XhoI and KpnI (forward, 5'-XhoI-AACCTCGAGAGCGAT GGCAAACCGGTG-3'; reverse, 5'-KpnI-GTTGGTACCTTA TTTGTTCAGCGCT-3').…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar result had also been reported by another research group (Huang, Gronthos, & Shi, 2009). However, other studies using constructs with burst release of SDF-1α in the early stage demonstrated successfully the recruitment of BMSCs (Dashnyam et al, 2014;He, Ma, & Jabbari, 2010;Ji et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Similar result had also been reported by another research group (Huang, Gronthos, & Shi, ). However, other studies using constructs with burst release of SDF‐1α in the early stage demonstrated successfully the recruitment of BMSCs (Dashnyam et al., ; He, Ma, & Jabbari, ; Ji et al., ). Therefore, further investigation is needed to confirm the recruitment of GFP‐positive rat BMSCs in the periodontal defect, and higher dose of SDF‐1α might be considered.…”
Section: Discussionmentioning
confidence: 99%